La villa umanistica nella cultura architettonica del primo Rinascimento - Rinaldi, Alessandro (Opus Incertum, 2019)
Recent historiography tends to see in the return to antiquity undertaken by humanistic culture, instead of the safe retreat into a universe of established certainties, the gamble of an adventure to an uncertain destination. Antiquity is in fact to be wholly reconstructed and reinvented starting from a fragmentary and problematic documentation. The reconstruction work is particularly difficult in the context of residential architecture and becomes impossible in the case of the villa. The almost total absence of direct archaeological evidence is combined with the strong personality of an architectural genre that in the late Medieval age found a very persuasive definition. This is why antiquity can manifest itself only in the form of an episode inserted in the frame of a Medieval building.